Obsidian sourcing analysis by X-ray fluorescence (XRF) for the Neolithic sites of Slavnaya 4 and 5, Sakhalin Islands (Russia). (December 2017) - Izuho, Masami; Ferguson, Jeffrey R.; Vasilevski, Alexander; Grishchenko, Vyacheslav; Yamada, Satoru; Oda, Noriyoshi; Sato, Hiroyuki
Abstract: Here we report the results of obsidian sourcing analysis by XRF for 13 specimens in total from the two Neolithic sites of the Slavnaya 4 and 5 on Sakhalin Islands (Russia). The results show that stone tools and blade cores from Slavnaya 4 and 5 sites were made of obsidian from two sources on Hokkaido (Japan): Shirataki-Akaishiyama and Oketo-Tokoroyama. Evidence of on-site reduction of two blade cores from Shirataki Akaishiyama obsidian suggest that the Neolithic people transported sizeable blade cores > 400 km from the source for the purpose of primary blade reduction to supply blanks for tool manufacture.